E-125 Specialty provider distribution of endovascular neurointerventions of the head and neck – an appraisal. (22nd July 2018) - Atsina, K; Cox, M; Hurst, R; Parker, L; Levin, D
Abstract : Purpose: In recent years, improving technology, safety and efficacy of percutaneous endovascular neuro-interventions (ENIs), has generated interest among various specialty groups in catheter-based therapies. We previously demonstrated that the neurovascular triad (radiology, neurosurgery, and neurology) had a large presence in the performance of intracranial ENIs, although other groups predominate vascular interventions in the neck. The purpose of this study is to appraise the afore-stated information with new data reflecting changes in CPT coding, and to assess any changes in the involvement of radiologists, neurosurgeons, and other physicians in the performance of ENIs. Methods: The Medicare Part B fee-for-service databases for 2015–2016 (covering 37.5 million enrollees in 2015) were the data source. We selected the CPT codes for ENIs of the head and neck. The databases provided nationwide Medicare volumes for those codes, as well as the specialties of the providers utilizing these codes. We compared ENI volumes and utilization rates by radiologists, neurosurgeons, neurologists, cardiologists, vascular surgeons and other physicians. Results: Since 2013, the total volume of ENIs of the head and neck performed increased from 15 625 to 26 865 in 2015 and 21 992 in 2016 respectively. Of these volumes, radiologists performed 39% in 2015 and 35% in 2016 respectively, compared with 38% and 35% respectively by neurosurgeons, 10% and 13% respectively by cardiologist, and 5% and 7% respectively by both neurologist and vascular surgeons. For intracranial procedures only, both radiologist and neurosurgeons performed 47% (Radiology: 54% and Neurosurgery: 33% in 2013) of procedures in 2015, and 44% by radiologist and 47% by neurosurgeons respectively in 2016 comprising the majority. Cardiologists (45% in 2015, and 40% in 2016) and vascular surgeons (20% in 2015, and 23% in 2016) performed the majority of extracranial ENIs, with approximately 98% of their procedures being carotid artery stenting procedures. Conclusion: Since 2013, patient utilization rates of ENIs increased 1.7 times in 2015 and 1.4 times in 2016. The largest clinical specialties that engage in ENIs continue to be radiology and neurosurgery, largely performing intracranial ENIs, and with cardiologist and vascular surgeons largely performing extracranial ENIs. Despite minor fluctuations in the subtypes of ENIs performed from year to year, radiologists continue to maintain a large presence in the performance of ENIs of the head and neck, with neurosurgery performance volumes steadily rising. The continued increase in ENI volumes should reflect a good market environment for aspiring neuro-interventional trainees, particularly from radiology, neurosurgery, and neurology backgrounds. Disclosures: K. Atsina: None. M. Cox: None. R. Hurst: None. L. Parker: None. D. Levin: None.